(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
The Legend Beach-Pamekasan is a tourist destination surrounded by five monitoring stations, where contamination by Escherichia coli bacteria has been detected. This bacterium can proliferate rapidly in aquatic environments when sufficient nutrients, particularly total organic matter, are present. Therefore, this study aims to assess the suitability of The Legend Beach-Pamekasan for tourism based on E. coli abundance and to analyze the relationship between total organic matter concentration and E. coli abundance at the study site. Bacterial abundance was determined using the membrane filtration method following ISO 9308-1:2014, while total organic matter content was analyzed based on SNI 06-6989.22-2004. The results indicate that E. coli abundance at Station 7 (The Legend Beach-Pamekasan) falls within the safe threshold for recreational beach use at 30 CFU/mL. However, swimming and snorkeling activities are not recommended in the surrounding waters, as E. coli levels at Station 1 (estuary) and Station 3 (fish-washing waste area) exceed the quality standard threshold established by Republic of Indonesia Government Regulation No. 22 of 2021. A significant correlation was found between total organic matter concentration and E. coli abundance across all stations (ρ = 0.01, p < 0.05). These findings highlight the need for effective waste management strategies in the area to prevent further contamination and ensure the long-term sustainability of The Legend Beach-Pamekasan as a safe and viable tourism destination.